2013
DOI: 10.1186/1742-4755-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Family size preference and factors affecting the fertility rate in Hyogo, Japan

Abstract: BackgroundJapan has consistently shown a low fertility rate, which has been lower than the replacement level since 1974, and represents one of the least fertile countries in the world. This study was designed to determine the family size preference of and its effect on Japanese women.MethodsWe conducted a questionnaire survey among women who visited the obstetrics and gynecology department of 18 hospitals and clinics in the Hyogo Prefecture, Japan, between October 2011 and February 2012. All the women were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…The findings of our study also showed that the increasing education of women was correlated with reduced expected number of children ( 46 , 53 ) Based on conducted studies, the place of residence can affect childbearing or the number of CEB by a woman ( 54 , 55 ). Usually, the number of children in rural areas is more than urban areas which were also found in our results ( 8 , 56 ). Employed or higher-educated women are more likely to live in urban ( 57 ).…”
Section: Discussionsupporting
confidence: 88%
“…The findings of our study also showed that the increasing education of women was correlated with reduced expected number of children ( 46 , 53 ) Based on conducted studies, the place of residence can affect childbearing or the number of CEB by a woman ( 54 , 55 ). Usually, the number of children in rural areas is more than urban areas which were also found in our results ( 8 , 56 ). Employed or higher-educated women are more likely to live in urban ( 57 ).…”
Section: Discussionsupporting
confidence: 88%
“…Preterm birth (PTB) is defined as parturition before 37 weeks of gestation and approximately 15 million babies are born prematurely each year [ 1 ]. In Korea, the rate of PTB has continuously increased, from 4.8 % to 2008 to 7.8 % in 2018 [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the location of the participants was skewed towards urban areas in this study. It is necessary to consider rural-urban differences such as mental health of perinatal women, 25 family size, 26 and health-seeking behavior. 27 It should be noted that the 25th, 50th, 75th, and 90th percentile values reported in this study are not normative data for Japanese infants, not only because of insufficient adjustment for J o u r n a l P r e -p r o o f 16 covariates, but also because of the methods of data collection.…”
Section: Discussionmentioning
confidence: 99%